ENDOGEN INTERFERON INDUKSIYA BO`LISHIDA ORGANIZMNING GIPOREAKTIVLIK HOLATI VA UNI BARTARAF ETISH USULLARI (Conferencea, 2022)
This article discusses the medicinal properties and activity of Gossypium and its physiologically active derivatives isolated from plants in relation to viral and other infectious diseases. The period of hyperactivity of drugs rometin and megoferon was analyzed. Gossypol and megosine have been comparatively studied in animals. It has been established that gossypol derivatives - rometin and megoferon induce interferon synthesis at a high rate (up to 512─1024 unit/milliliter) compared to gossypol and improve water solubility. To eliminate the refractory state in the body, it is advisable to combine the first inductor and the second inductor.